Analysis of the Influence of Brand Advertising and Brand Attachment on Consumer Purchasing Decisions in the Fashion Industry - Azizah, Zainab; Al Adawiyah, Rumaisah Azizah; Mussanadah, Atik Ul (Management Analysis Journal, 2024)
This study aims to analyze the influence of brand advertising and brand attachment on consumer purchasing decisions in the fashion industry. This study is motivated by the importance of understanding marketing strategies that can drive consumer behavior amidst increasingly competitive brand competition. A quantitative approach was used in this study, with a survey method through online questionnaire distribution to randomly selected respondents. A total of 172 valid respondents participated in this study. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique through SmartPLS software. The results showed that brand advertising had a significant effect on brand attachment (β = 0.628; T = 14.79; p <0.001) and on purchasing decisions (β = 0.377; T = 4.22; p <0.001). In addition, brand attachment also had a significant effect on purchasing decisions (β = 0.238; T = 2.35; p = 0.019). These findings indicate that effective advertising strategies can not only increase consumer brand attachment but also directly and indirectly drive purchasing decisions. Therefore, companies in the fashion industry need to integrate emotional approaches in advertising to strengthen brand attachment and create consumer loyalty.